2013
DOI: 10.1007/s00484-012-0624-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of air-suspended particulate concentration on the incidence of suicide attempts and exacerbation of schizophrenia

Abstract: The main objective of this study was to evaluate the role of the concentration of solid air-suspended particles (SSP) in the incidence of mental disorders. The study is based on 1,871 cases, registered in the Beer-Sheva Mental Health Center (BS-MHC) at Ben-Gurion University (Israel) during a 16-month period from 2001 to 2002; 1,445 persons were hospitalized due to exacerbation of schizophrenia (ICD-10: F20-F29) and 426 after committing a suicide attempt using a variety of means as coded in the ICD-10 (ICD-10: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…A compelling case for the involvement of early life air pollution (AP) exposures and ASD is suggested by a growing number of epidemiological studies (Volk et al, 2013, 2014, 2011; Becerra et al, 2013; Jung et al, 2013; Roberts et al, 2013a; Windham et al, 2006; Kalkbrenner et al, 2010). AP has also been linked to impaired cognitive abilities (Wang et al, 2009; van Kempen et al, 2012), and attention-related deficits (Siddique et al, 2011) as well as to schizophrenia (Duan et al, 2018; Eguchi et al, 2018; Yackerson et al, 2013; Pedersen et al, 2004), notably all neurobehavioral disorders with male-biased prevalence rates. These disorders also frequently include abberant social behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A compelling case for the involvement of early life air pollution (AP) exposures and ASD is suggested by a growing number of epidemiological studies (Volk et al, 2013, 2014, 2011; Becerra et al, 2013; Jung et al, 2013; Roberts et al, 2013a; Windham et al, 2006; Kalkbrenner et al, 2010). AP has also been linked to impaired cognitive abilities (Wang et al, 2009; van Kempen et al, 2012), and attention-related deficits (Siddique et al, 2011) as well as to schizophrenia (Duan et al, 2018; Eguchi et al, 2018; Yackerson et al, 2013; Pedersen et al, 2004), notably all neurobehavioral disorders with male-biased prevalence rates. These disorders also frequently include abberant social behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…According to the hypothesis of neuroinflammation, air contaminants could cause an increase in cytokines and reactive oxygen species, and consequently self-aggressive behavior [ 14 , 15 ]. The causal mechanisms between air pollution and suicide might not only involve this direct pathway via inflammation, but also the exacerbation of mental disorders that increase the risk of suicidal behavior [ 16 , 17 ]. Nonetheless, these pathways are not yet clearly established, and are far from being biologically proven.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, epidemiological studies have reported associations between daily air pollution and hospital admissions or emergency room visits for Parkinson's disease (Zanobetti et al. 2014) and neuro-psychological responses such as depression and suicide attempt/mortality (Bakian et al 2015; Kim et al 2010; Szyszkowicz et al 2009; Szyszkowicz et al 2010; Yackerson et al. 2014).…”
Section: Introductionmentioning
confidence: 99%